Towards evidence-based urban planning: A composite index approach to liveability assessment - Niharika Tiwari; Vinod Kumar Tripathi (National Geographical Journal of India, 2025)
Urban liveability is increasingly acknowledged as a central theme in urban geography, planning, and sustainable development. The quality of urban life depends not only on physical infrastructure but also on social, economic, and governance dimensions that collectively determine the well-being of residents. This paper develops a Composite Urban Liveability Index (CULI) to evaluate the liveability of four major municipal corporations in Uttar Pradesh, India: Prayagraj, Lucknow, Kanpur, and Varanasi. Using secondary data sources from government offices, census reports, international agencies, and planning authorities, thirty-one objective indicators were identified across four dimensions: socio-infrastructure, economic, governance, and environmental. The data were standardized and analysed using Principal Component Analysis (PCA) with varimax rotation to reduce dimensionality and extract principal components. The results reveal three significant components: socio-infrastructure, economic, and governance-environmental indicators. Lucknow emerged as the most liveable city with a CULI score of 1.5030, followed by Prayagraj (1.3005), Kanpur (0.9099), and Varanasi (0.5437). These findings highlight significant inter-city disparities in liveability within Uttar Pradesh, with implications for sustainable urban planning and governance. The paper contributes to the ongoing discourse on urban liveability by proposing a composite, statistically validated index that can be used by policymakers to assess, monitor, and elevate the overall well-being of residents in Indian cities.